Ovarian cancer risk is reduced by prolonged lactation: A case-control study in southern China - Su, D.; Pasalich, Maria; Lee, Andy; Binns, Colin (American Society for Nutrition, 2013)
Background: Ovarian cancer is an important neoplasm that is difficult to diagnose and treat; therefore, prevention is the preferable strategy. Growing evidence indicates a protective effect of breastfeeding on ovarian cancer risk. Objective: The objective was to investigate the association between lactation and the risk of ovarian cancer among southern Chinese women. Design: A case-control study was undertaken in Guangzhou, Guangdong Province, between August 2006 and July 2008. A validated and reliable questionnaire was used to obtain information on the months of lactation and number of children breastfed in a sample of 493 incident ovarian cancer patients and 472 hospital-based controls (mean age: 59 y). Logistic regression analyses were performed to assess the association between breastfeeding and the risk of ovarian cancer. Results: Significant inverse dose-response relations were found for both duration of lactation and the number of children breastfed. The adjusted ORs were 0.09 (95% CI: 0.04, 0.19) for women with ≥31 mo of total lactation and those with ≤10 mo of lactation and 0.38 (95% CI: 0.27, 0.55) for women with ≥3 children breastfed compared with those with one child breastfed. Conclusion: Prolonged lactation is associated with a lower risk of ovarian cancer in parous Chinese women.